Creation of a Human-in-the-Loop Simulator Environment for Fifth Generation Stressor Research - Miltenburg, M.P.G. van; Foorthuis, L.R.; Zon, G.D.R. (NTSA, 2023)
The introduction of fifth generation platforms has led to a more information-driven air operation. It is characterized by the communication between different platform types within a mission and an increased operator autonomy due to improved information availability. Current research lacks understanding of the subtle differences between fourth and fifth generation stressors. Consequently, this requires additional knowledge on the interaction between stressors induced by fifth generation operations and human performance. The fundamental challenge is to create a research environment in which (1) multiple fifth generation platforms operate together and (2) the equipment to measure impact of stressors on the operator is integrated. A second challenge is to generate scenarios that can be used in a research environment in which traditional (e.g. fourth generation) and potential new (e.g. fifth generation) stressors can be generated and manipulated. This paper describes the design of a research environment, which is suitable to measure the effects of these stressors. The research environment consisted of an F-35 and an MQ-9 simulator with human operators. Mission scenarios were generated to simulate both traditional and potential new stressors. Workload and stress levels were measured using functional near-infrared spectroscopy (fNIRS), electrocardiography (ECG), and the NASA Task Load Index. An experimental evaluation was carried out with former F-16 pilots using the developed missions and research environment. The evaluation results showed that the research environment can be used operationally and the equipment is able to measure impact of stressors on the operator. Furthermore, the environment allowed dynamic adjustment of scenario complexity during experiments, enabling adaptation to pilot performance. The research environment opens up possibilities for further generation specific stress-mitigation and training methodology development research. Ultimately, the study paves the way for future research on the impact of fifth generation platforms and operations on human performance.